ERROR ANALYSIS OF WORD ORDER USED IN WRITING RECOUNT TEXT MADE BY STUDENTS’ AT SMK NEGERI 1 PINRANG - Nurul Fitrah Syams; Abdul Muis Said (Universitas Islam Negeri Alauddin Makassar, 2016)
The objective of this research was to find out the kind of errors that often occurred in the use of the word order in recount text made by student at SMKN 1 Pinrang. To analyze the data, the writer used descriptive qualitative method and used error analysis procedure. The participants of this study consist of 30 students from the grade XI of Accounting 3 at SMK Negeri 1 Pinrang. The data were taken by using tests of writing. By this writing test, the writer found errors as follows: the errors of using the correct verb (45.41 percent), the errors of using the correct to be (30.28 percent) and the errors of using the correct noun phrase (24.31 percent). Based on the finding and discussion of the research, the researcher concluded that the most common error that made by the students is using verb. Based on the finding and discussion of the result, the researcher concluded that the students still faced difficulties in using word order.